OUTCOME AND EFFECTIVENESS OF ULTRASONICALLY ACTIVATED IRRIGATION ON ROOT CANAL DISINFECTION AND PERIAPICAL HEALING. A SYSTEMATIC REVIEW. - Suhael Ahmed, Sultan Ismail Alshammari, Mohammed Abdallah Almana, Sultan Khalid Alsuayri, Ohoud Hamoud Alshammari, Shouq Mohammed Aljohani, Renad Mohammed Alasmari, Aljowhara Allaboon, Farhan Jassam AlShammary (Chelonian Research Foundation, 2022)
Irrigation is an essential part of root canal treatment because it improves the debridement and disinfection of areas that tools are unable to thoroughly clean. Remote parts of the root canal system are frequently difficult to clean using irrigation that is mostly done with a syringe and a needle. As a result, various more complex techniques have been introduced. Ultrasonic irrigant activation is probably the most widely used adjunct method, and it has been compared with syringe irrigation in multiple studies. However, very few attempts have been made to summarize the available evidence. Aim: The purpose of this study was to compare the effectiveness of ultrasonic irrigant activation during primary root canal treatment of mature permanent teeth to syringe irrigation in terms of cleansing and disinfecting root canals and healing of apical periodontitis. Methods: An electronic search was conducted of the Cochrane Library, Embase, PubMed, Web of science and Scopus databases using both free-text key words and controlled vocabulary. Additional studies were sought through hand searching of endodontic journals and textbooks. The retrieved studies were screened by 2 reviewers according to predefined criteria. The included studies were critically appraised, and the extracted data were arranged in tables. Results: The manual and automated searches turned up 957 titles, out of which 8 articles were selected for the systematic review. This evaluation comprised of randomized trials and in vitro research. In comparison to syringe irrigation, ultrasonic activation did not speed up the healing of apical periodontitis in teeth having a single root canal. The in vitro microbiological research reported a range of contradictory findings. Ultrasonic activation was superior to syringe irrigation in the removal of pulp tissue fragments and hard tissue debris. Conclusion: As a result of inadequate evidence that was provided, no firm clinical recommendations could be made although ultrasonic activation does provide an alternate debridement mode in curved root canals. Key Words- cleaning, disinfection Apical periodontitis, irrigation, root canal, ultrasonic activation